2006
DOI: 10.1161/01.res.0000220643.65941.8d
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Gene Induction and Protection From Ischemia/Reperfusion Injury in the Hearts of Transgenic Mice With a Tamoxifen-Regulated Form of ATF6

Abstract: Abstract-Ischemia/reperfusion (I/R) affects the integrity of the endoplasmic reticulum (ER), the site of synthesis and folding of numerous proteins. Therefore, I/R may activate the unfolded protein response (UPR), resulting in the induction of a collection of ER stress proteins, many of which are protective and function to resolve the ER stress. In this study, we showed that when mouse hearts were subjected to ex vivo I/R, the levels of 2 ER stress-inducible markers of the UPR, the ER-targeted cytoprotective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
271
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(287 citation statements)
references
References 43 publications
12
271
1
3
Order By: Relevance
“…Studies in transgenic mice expressing the activation transcription factor 6, ATF6, also suggest that ER stress may participate in ischemia-reperfusion injury [9]. During ischemia-reperfusion injury, ER stress may be excessively activated, since in addition to the increased expression of the chaperone protein, GRP78, there is a significant increase in the pro-apoptotic kinase, phosphorylated-JNK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in transgenic mice expressing the activation transcription factor 6, ATF6, also suggest that ER stress may participate in ischemia-reperfusion injury [9]. During ischemia-reperfusion injury, ER stress may be excessively activated, since in addition to the increased expression of the chaperone protein, GRP78, there is a significant increase in the pro-apoptotic kinase, phosphorylated-JNK.…”
Section: Discussionmentioning
confidence: 99%
“…δPKC translocation to the ER mediates, at least in part, ER stress response of the myocardium in a model of ischemia-reperfusion injury Inhibition of δPKC protects the heart from ischemia-reperfusion injury partly through reducing mitochondria-mediated cell death [13,16]. Increasing evidence suggests that ischemia/ reperfusion in the heart also activates the ER stress response resulting in cellular injury [5,8,9,[30][31][32]. Based on our in vitro results, we next determined whether inhibition of δPKC protects the myocardium from ER stress in an ex vivo model of ischemia and reperfusion injury.…”
Section: δPkc Translocates To the Endoplasmic Reticulum Following Tunmentioning
confidence: 99%
See 2 more Smart Citations
“…Martindale et al obtained results inconsistent with the above opinions. They suggested that the UPR is activated in the heart during I/R, and as a result, the ATF6 branch of UPR-induced expression of proteins, including GRP78 and GRP94, can reduce I/R injury [109] . I/R injury rats are accompanied by myocardial infarction (MI), and increased myocardial infarct size and myocardial enzyme activity were observed [106] .…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%